Genetic selection for postweaning growth rate shows no relevant negative impact on reproductive performance in breeding rabbit does - P.J. Marín-García; E. Martínez-Paredes; L. Ródenas; T. Larsen; M. Cambra-López; E. Blas; J.J. Pascual (Animal)
Genetic selection for growth rate has often been related with potential negative effects on various reproductive traits across different species. Using rabbit as a model, this study has evaluated for the first time how genetic selection for growth rate has affected feed efficiency, resource allocation, blood traits, reproductive performance and survival during five reproductive cycles in rabbit does. To this end, we used 88 reproductive rabbit females from two vitrified and rederived populations of the same paternal line, differing only in 18 generations of genetic selection for growth rate (n = 44 for R19V and n = 44 for RV37V). Selection for growth rate did not affect apparent nutrient digestibility coefficients in multiparous lactating rabbit females. However, due to reproductive problems, a higher number of R37V females were culled before the first parturition with respect to R19V females (34 vs 11%, respectively; P < 0.01). At first mating, R37V females showed higher perirenal fat thickness (+5.3%; P < 0.001) but lower non–esterified fatty acids and fructosamine content in the blood (−43.2 and −24.1%, respectively; P < 0.05) than R19V females. R37V females showed increased BW at weaning (+18.4%; P < 0.01). This difference was maintained over the R19V females until the first parturition. In the first reproductive cycle, R37V females exhibited lower fertility (−16.5 percentage points; P < 0.05), but higher prolificacy than R19V females (+1.94 liveborn kits; P < 0.05). Selection for postweaning growth rate did not affect feed intake, milk yield and fertility of reproductive rabbit females throughout the five reproductive cycles. However, R37V females had higher perirenal fat thickness at parturition and 18 and 28 days postpartum than R19V females (+4.7, +3.8 and +3.8%, respectively; P < 0.05). Litters from R37V females tended to have a higher size at birth before standardisation (+1.1 total kits; P < 0.10), as well as heavier litter weight at weaning (+10.4%; P < 0.05), than those from R19V females. In conclusion, genetic selection for postweaning growth rate shows no relevant negative impact on reproductive performance in breeding rabbit does.